Acute cold stress in rheumatoid arthritis inadequately activates stress responses and induces an increase of interleukin 6. Issue 4 (15th April 2008) - Straub, R H; Pongratz, G; Hirvonen, H; Pohjolainen, T; Mikkelsson, M; Leirisalo-Repo, M
Abstract : Objective: Acute stress in patients with rheumatoid arthritis (RA) should stimulate a strong stress response. After cryotherapy, we expected to observe an increase of hormones of the adrenal gland and the sympathetic nervous system. Methods: A total of 55 patients with RA were recruited for whole-body cryotherapy at −110°C and −60°C, and local cold therapy between −20°C and −30°C for 7 days. We measured plasma levels of steroid hormones, neuropeptide Y (sympathetic marker), and interleukin (IL)6 daily before and after cryotherapy. Results: In both therapy groups with/without glucocorticoids (GC), hormone and IL6 levels at baseline and 5 h after cold stress did not change over 7 days of cryotherapy. In patients without GC, plasma levels of cortisol and androstenedione were highest after −110°C cold stress followed by −60°C or local cold stress. The opposite was found in patients under GC therapy, in whom, unexpectedly, −110°C cold stress elicited the smallest responses. In patients without GC, adrenal cortisol production increased relative to other adrenal steroids, and again the opposite was seen under GC therapy with a loss of cortisol and an increase of dehydroepiandrosterone. Importantly, there was no sympathetic stress response in both groups. Patients without GC and −110°C cold stress demonstrated higher plasma IL6 compared to the other treatment groups (not observed under GC), but they showed the best clinical response. Conclusions: We detected an inadequate stress response in patients with GC. It is further shown that the sympathetic stress response was inadequate in patients with/without GC. Paradoxically, plasma levels of IL6 increased under strong cold stress in patients without GC. These findings confirm dysfunctional stress axes in RA.